The Effects of Shallow Cryogenic Process On The Mechanical Properties of AISI 4140 Steel - Eşref KIZILKAYA; İsmail OVALI (Gazi Üniversitesi Fen Bilimleri Dergisi, 2018)
In this study, shallow cryogenic treatments were carried out for various holding time to AISI 4140 steel and the effects of heat treatment parameters on wear behavior, impact strength and tensile strength were investigated. Three different holding times were used for cryogenic heat treatments. After the cryogenic process, single tempering was applied. In addition, the abrasion tests were carried out at three different forces (5N, 10N and 15N) at a constant slip speed (3.16 m / s) and at three different slip distances (95 m, 190 m, 285 m). It has been determined that the shallow cryogenic process parameters significantly influence the mechanical properties of the AISI 4140 steel as a result of experimental studies., Low heat treatment times in cryogenic heat treatment have been found to have a positive effect on many mechanical properties, especially wear. The mechanical properties of the AISI 4140 steel can be optimized by controlling the shallow cryogenic heat treatment parameters.